For debate: consensus injury definitions in team sports should focus on missed playing time - Orchard, J.; Hoskins, W.; Chiro, M. (Clinical Journal of Sport Medicine, 2007)
Objective: To compare the most commonly used and proposed injury definitions for surveillance systems in team sports and attempt to assess their suitability for consensus definitions in terms of reliability and functionality.